Stabilizer Kamera 2 axis dengan Kontrol Proporsional Integral Derivatif (PID) Berbasis LabView - Anjasmara A (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2015)
Abstract - In taking a video on the camera results that are not much movement are needed, so that the video can be seen properly by the audience. In addition, the video does not have a lot of distortion which is caused by being unstable in its capture. Then a Camera Stabilizer is needed so that the resulting video remains stable. This camera stabilizer uses a computer device in making this program needed to make it easier for the operator to set the desired angle. In order to obtain the best stability, a tuning of the Proportional Integral Derivative (PID) controller parameter is performed. In this tuning we can find out the values of Proportional gain (Kp), Integral Time (Ti), and Derivative Time (Td). The PID controller can provide action to the servo motor controller based on the error obtained, the desired servo motor rotation value is called the setpoint. LabView software is used as a driver, motor speed control. Keyword : LabView, servo motor, arduino, accelerometer, computer